A comprehensive analysis of induced pluripotent stem cell (iPSC) production and applications - Matiukhova, Margarita; Ryapolova, Anastasia; Andriianov, Vladimir; Reshetnikov, Vasiliy; Zhuravleva, Sophia; Ivanov, Roman; Karabelsky, Alexander; Minskaia, Ekaterina (Frontiers in Cell and Developmental Biology, 2025)
The ability to reprogram mature, differentiated cells into induced pluripotent stem cells (iPSCs) using exogenous pluripotency factors opened up unprecedented opportunities for their application in biomedicine. iPSCs are already successfully used in cell and regenerative therapy, as various drug discovery platforms and for in vitro disease modeling. However, even though already 20 years have passed since their discovery, the production of iPSC-based therapies is still associated with a number of hurdles due to low reprogramming efficiency, the complexity of accurate characterization of the resulting colonies, and the concerns associated with the safety of this approach. However, significant progress in many areas of molecular biology facilitated the production, characterization, and thorough assessment of the safety profile of iPSCs. The number of iPSC-based studies has been steadily increasing in recent years, leading to the accumulation of significant knowledge in this area. In this review, we aimed to provide a comprehensive analysis of methods used for reprogramming and subsequent characterization of iPSCs, discussed barriers towards achieving these goals, and various approaches to improve the efficiency of reprogramming of different cell populations. In addition, we focused on the analysis of iPSC application in preclinical and clinical studies. The accumulated breadth of data helps to draw conclusions about the future of this technology in biomedicine.